Selection for pollen competitive ability in mixed‐mating systems. (27th September 2018) - Peters, Madeline A. E.; Weis, Arthur E.
Abstract: Coexpression of genes in plant sporophytes and gametophytes allows correlated gametic and sporophytic selection. Theory predicts that, under outcrossing, an allele conferring greater pollen competitive ability should fix within a population unless antagonistic pleiotropy with the sporophyte stage is strong. However, under strong selfing, pollen competitiveness is immaterial as superior and inferior competitors are deposited on opposite stigmas, producing assortative competition. Because many plant species have mixed‐mating systems, selfing should be critical in the spread and maintenance of pollen‐expressed genes affecting competitiveness. We present two one‐locus, two‐allele population genetic models for the evolution of a locus controlling pleiotropic antagonism between pollen competitiveness and diploid fitness. Analytical solutions provide minimum and maximum selfing rates allowing invasion of alleles with greater diploid and haploid fitness, respectively. Further, polymorphism is only maintained when diploid selection is recessive. Fixation of the allele conferring greater pollen competitiveness may be prevented, even with weak sporophytic counterselection, with sufficiently high selfing. Finally, selfing expands and limits the range of haploid–diploid selection coefficients allowing polymorphism, depending on dominance and selfing mode.